Binding determinants of the small heat shock protein, αB-crystallin: recognition of the 'IxI' motif - Delbecq, Scott P; Jehle, Stefan; Klevit, Rachel (The EMBO journal, 2012)
Small heat shock proteins (sHSPs) play a central role in protein homeostasis under conditions of stress by binding partly unfolded, aggregate‐prone proteins and keeping them soluble. Like many sHSPs, the widely expressed human sHSP, αB‐crystallin (‘αB’), forms large polydisperse multimeric assemblies. Molecular interactions involved in both sHSP function and oligomer formation remain to be delineated. A growing database of structural information reveals that a central conserved α‐crystallin domain (ACD) forms dimeric building blocks, while flanking N‐ and C‐termini direct the formation of larger sHSP oligomers. The most commonly observed inter‐subunit interaction involves a highly conserved C‐terminal ‘IxI/V’ motif and a groove in the ACD that is also implicated in client binding. To investigate the inherent properties of this interaction, peptides mimicking the IxI/V motif of αB and other human sHSPs were tested for binding to dimeric αB‐ACD. IxI‐mimicking peptides bind the isolated ACD at 22°C in a manner similar to interactions observed in the oligomer at low temperature, confirming these interactions are likely to exist in functional αB oligomers. Cytoprotective small heat‐shock proteins display an intrinsic affinity for their C‐termini in solution, providing candidate binding sites for both sHSP function and oligomerization.